Biomass-based value webs and food security in Africa: The case of maize value web in Nigeria - O.A. Oyedeji; R.O. Babatunde; O.E. Ayinde; A.H. Adenuga (World Development Sustainability)
Food insecurity and widespread hunger remains high in sub-Saharan Africa, while demand for non-food agricultural products continues to rise. Biomass-based value web concept can help improve household food security for the poor through increased food production, while providing enough non-food, processed biomass to provide employment and income opportunities. However, there is limited information on the impact of the concept on household food security. This study was undertaken to examine the impact of maize biomass value web on food security of farming households in Nigeria. The study employed a multi-stage random sampling method to sample 288 farming households in Nigeria who were administered a well-structured questionnaire. The statistical tools used for the analysis were descriptive statistics, food security analysis and regression techniques. The result of the study shows that households put maize into seven predominant uses in the study area. It was also found that the majority (63.9 %) of households have a low level of participation in the maize biomass value web. The household head age, gender, credit access of household head, education in years, household infrastructure index, total farm size, quantity of maize harvested, and asset value are the significant factors driving household participation in the maize value web. In addition, maize biomass value web participation positively and significantly affects household food security. The study concludes that increased participation in the biomass value web will likely improve the food security of Nigerian citizens, especially the rural poor farmers.